A comprehensive pathway on the determination of the kinetic triplet and the reaction mechanism of brewer's spent grain and beech wood chips pyrolysis. (May 2022) - Dessì, Federica; Mureddu, Mauro; Ferrara, Francesca; Pettinau, Alberto
Abstract: This study paves a strategy to better understand the thermal conversion of biomass residues. In particular, a comprehensive study to determine the multi-step reaction model to describe the pyrolysis process of brewer's spent grain from Pilsner (PBSG) and Weizen (WBSG) malts, and beech wood chips (BWC) has been presented. The results of the kinetic triplet optimisation show that the process begins with a nth order reaction Fn ( n  = 1.74, 1.52, 1.54) for extractives, followed by Avrami-Erofeev type nucleation reactions An ( n  = 1.50, 1.50) for hemicellulose, with the exception of beech hemicellulose that follows the nth order mechanism Fn ( n  = 1.25), and An ( n  = 1.50, 1.50, 1.50) for cellulose, for PBSG, WBSG and BWC, respectively. Moreover, by virtue of the comprehensive approach proposed in this study, a single nth order mechanism Fn with n  = 1.19, 1.23, 1.32 for PBSG, WBSG and BWC, respectively, has been obtained for the lignin. The developed model has been used to support the design of a pilot-scale down-draft gasifier for the thermal valorisation of brewer's spent grain. Graphical abstract: Image 1